Leadership and Solidarity Business Structure in Colombian Artisanal Fishing - Luque Berkowitz, Jorge Iván; Rua Castañeda, Sohely (Cooperativismo & Desarrollo, 2014)
This study presents an overview of the leadership at Colombian artisanal fishing solidarity organizations, along with the problems they face in their social and entrepreneurial strengthening. The qualitative approach analysis is based on semi-structured interviews with leaders from diverse organizations and associative forms of artisanal fishing in particular. The findings indicate that solidarity leaderships face an ethical and operative dilemma with respect to the democratic management formula and progress in their entrepreneurial structure. In the specific case of artisanal fishing, the socio-environmental context poses a challenge to its competitive position. The conclusion is that there is a need to generate a balanced entrepreneurial vision that would provide sustainability for this economic activity in accordance with the challenges in the context, and that cooperative principles must be applied in harmony with this effort, which signifies recognizing personal and collective interests, differentiated levels of participation and the development of technical-operative capacities for managing associative enterprises.